ANALISIS PERENCANAAN LABA DAN RESIKO USAHA DALAM PRODUKSI SIR 20 DI PT. PERKEBUNAN NUSANTARA (PTPN) VII (PERSERO) UNIT PADANG PELAWI - Sitorus, Windarti; Arianti, Nyayu Neti; Romdhon, M. Mustopa (Jurnal AGRISEP, 2018)
The purposesof this study were to analyze the profit planning in the production of SIR 20 and determine the level of business risk from profit targets at PTPN VII (Persero) Unit Padang Pelawi. The secondary data were obtained from company started from January 2014 to December 2015. The results showed that the profit planning with the application of the analysis of CVP (Cost-Volume-Profit) for 2015 have not been effective and efficient or in the other words, PTPN VII (Persero) Padang Pelawi Unit had failed to achieve the profit target as planned. This is due to an event beyond the normally occurring either at PTPN VII (Persero) Unit Padang Pelawi and globally selled seller by prices SIR 20 increasingly falling both inside and outside of the country in 2015. Then, for the risk analysis when seen from the criteria of assessment, the value of CV> ½ and L <0 then there was a chance that will be borned at PTPN VII (Persero) Unit Padang Pelawi if the company achieve profit targets that have been planned. Possible risk wasthe risk of revenue caused by low amount of raw materials that gone into PPKR bokar due to lower selling prices offered by the company so the impact on sales of SIR 20 wasincreasingly reduced.